Inertial and geometrical segment parameters for female elite gymnasts - Leboucher, J.; Hars, M.; Pinti, A.; Dumas, G. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Knowledge of body segment parameters is essential in sport movement biomechanical analysis. These parameters, such as segment length, mass, moments of inertia as well as centre of mass location, are usually derived from anthropometric models. A sample of 30 national level female gymnasts was investigated in order to create a database for body segment parameters. Statistical analysis of the data from this group allowed for the designed of a new anthropometric model devoted to elite female gymnasts. Data acquisition was performed using an optical measurement system and some of the parameters were also assessed with direct measurements. Data analysis demonstrated that some segment linear regression modelling was accurate but some other were not pertinent. This study demonstrated homogeneity of a group of female gymnasts. The design of this study could be easily extended to other sport performers.